2013
DOI: 10.1111/j.1755-3768.2013.s100.x
|View full text |Cite
|
Sign up to set email alerts
|

A time‐line model of developmental events within the human fovea based on imaging and histology data

Abstract: Purpose To create a time‐line model of developmental events during normal maturation of the inner and outer foveal layers based on imaging and histological studies. Methods Data from recently published imaging studies using hand‐held OCT during the period following premature birth (Dubis et al. 2012; Maldonado et al., 2012; Vajkovic et al., 2012) and histology of normal donor eyes (Dubis et al., 2012; Hendrickson et al. 2012; Vajkovic et al., 2012) was used to establish the timing of foveal developmental event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Altogether, there seems to be independence between cone specialization and foveal pit formation as well as between ISe length and visual acuity . This supports a model in which the inner and outer part of fovea develops at different time frames, the inner part during late gestation and the outer part during the first postnatal years …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Altogether, there seems to be independence between cone specialization and foveal pit formation as well as between ISe length and visual acuity . This supports a model in which the inner and outer part of fovea develops at different time frames, the inner part during late gestation and the outer part during the first postnatal years …”
Section: Discussionsupporting
confidence: 79%
“…Sjöstrand & Popovic recently presented a time‐line model of developmental events within the human fovea. By merging data based on OCT imaging and histological samples they presented a model showing how the inner and outer part of the fovea matures within different time frames, the inner retina during the late part of gestation and the outer retina during the first postnatal years.…”
Section: Introductionmentioning
confidence: 99%
“…21 Analyses of spectral-domain OCT (SD-OCT) images of the fovea before and after full-term birth have shown the dynamic changes in different foveal layers from approximately 30 weeks of gestation through different stages of normal maturation. 21,22 In general, development follows a timeline with continuous increases in layer thicknesses, 23 but in some preterms with or without retinopathy the development of the inner retina is arrested at a certain stage. 24,25 In a previous study of preterms born extremely premature we found persisting signs of immaturity indicating retardation of several developmental events when imaged by lowresolution SD-OCT at an age of 6.5 years.…”
mentioning
confidence: 99%